Science Outreach At Madrasa Menggunakan Simulasi PhET (Physics Education Technology) : PHYSICS EDUCATION TECHNOLOGY - Pranata, Ogi Danika; Seprianto, Seprianto; Adelia, Ismi; Darwata, Siti Riva; Noperta, Noperta (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2022)
PhET (Physics Education Technology) is a technological product that contains a collection of interactive simulations for science learning. PhET simulations have been proven effective for various levels: high, middle, and elementary school. However, their implementation is tailored for each level. The implementation of PhET simulations for groups of students with varying levels or heterogeneous classes in science outreach is the main topic of this activity. Activity supports the enhancement of STEM literacy, which is an important aspect of life today. The science outreach activity, known as Ogirium: Mathematics and Science for Students, focuses on groups of students from different levels (heterogeneous classes). Community-based research was applied. There are 19 participants from various levels of students. At the end of the activity, students take a concept comprehension test. Subsequently, students receive feedback on the test results, and a questionnaire is given to gather participants' perceptions of the activity. This activity revealed three important findings: 1) science outreach activities are beneficial and can serve as alternative learning and empowerment for the community, 2) PhET is effective for the learning process in heterogeneous classes, and 3) science outreach in heterogeneous classes can create multidirectional cooperation, both among students from various levels and between teachers and students.